(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background : Industrial workers due to their long working hours which exposes them to various musculoskeletal and cardiopulmonary disorders. Long working hours and lack of proper health related guidelines to be followed during work they often overuse themselves which hampers their body mechanics and quality of life. studies have proved that ergonomic advice for low back pain and neck pain have improved satisfactorily the work capacity of the individuals. As far as authors knowledge, there is paucity in the literature targeting the awareness of ergonomic advice for industrial workers in rural areas, hence this study is been undertaken. Objectives : To identify ergonomic awareness of musculoskeletal disorders in small scale industrial workers and To identify ergonomic awareness towards respiratory disorders during work in small scale industrial workers. Results : 42% of people are aware about the necessary workplace health and safety training when starting job and there is a regular communication between employees and management about safety issue, 50% people are clear about their rights and responsibilities in relation to workplace health and safety and 47% people fell free to voice their concerns or make suggestions about workplace health and safety Conclusion : After carrying out a study of awareness of ergonomic principles in small scale industrial workers, we found out that industrial workers in small scale industries in india lack awareness about the occupational hazards and various safety regulations that are enacted in the betterment of employees.